Disaster Preparedness and Response Training in Batua Village, Makassar City - Noviyani Hartuti; Yoan Putri Praditia; Asyima; Ruqaiyah (SWAGATI : Journal of Community Service, 2025)
Flood disasters remain one of the most frequently occurring natural disasters in Indonesia, with Makassar City and Batua Village experiencing recurring inundation almost every year. Low levels of community knowledge and the absence of structured disaster preparedness training are key factors worsening disaster impacts. This community service program aimed to strengthen community-based disaster preparedness and response capabilities in Batua Village through participatory training involving BPBD Makassar, BMKG, PMI, and the Batua Community Health Center. Methods included workshops, lectures, simulations, and the establishment of a Village Disaster Response Team (KESTANA) comprising cadres, neighborhood leaders, youth, and health workers. Post-monitoring revealed positive outcomes: communities improved knowledge of flood prevention, disaster impact mitigation, early warning access, coordination channels, and evacuation data management. Overall, 78% of participants expressed positive responses. The program demonstrates that participatory, multi-stakeholder training effectively builds grassroots disaster resilience. Follow-up simulations and continuous capacity building are strongly recommended